God's New Whiz Kids? : Korean American Evangelicals on Campus. - Kim, Rebecca Y. (NYU Press, 2006)
In the past twenty years, many traditionally white campus religious groups have become Asian American. Today there are more than fifty evangelical Christian groups at UC Berkeley and UCLA alone, and 80% of their members are Asian American. At Harvard, Asian Americans constitute 70% of the Harvard Radcliffe Christian Fellowship, while at Yale, Campus Crusade for Christ is now 90% Asian. Stanford's Intervarsity Christian Fellowship has become almost entirely Asian. There has been little research, or even acknowledgment, of this striking development. God's New Whiz Kids? focuses on second-generat.